Isokinetic assessment of muscle imbalances and bilateral differences between knee extensores and flexores` strength in Basketball, Footbal, Handball and Volleyball Athletes - Teixeira, J.; Carvalho, C.; Moreira, C.; Santos, R. (International Journal of Sports Science, 2014)
The imbalance of muscle strength indicators is harmful for elite sport and, in case of significant asymmetries, it increases the probability of muscular injuries or the deterioration of the athletic performance. So it`s essential the evaluation of these imbalances in Handball, Basketball, Soccer and Volleyball athletes`. Objective: The aim of this study was to verify the existence of Isokinetic muscle imbalances in the profile of professional athletes from various modalities and examine their relationship with the sport practiced. Design: Through an observational, analytical and cross study were evaluated 86 athletes (Handball=14; Basketball=27; Football=25; Volleyball=20) using an isokinetic dynamometer Biodex Medical System 4 ®. The evaluated parameters were the Bilateral Differences and Hamstrings/Quadriceps Ratio at angular velocities of 60 °/s (4 repetitions) and 180 °/s (6 repetitions). Results: The Bilateral Differences (found) between the lower limbs are within the respected normal values (<10%). The Hamstrings / Quadriceps Ratio were higher in Football athletes and were lower in Volleyball athletes comparatively to other modalities. Conclusion: However, the motor skills of each sport do not seem to induce to significant muscular imbalances but each sport requires a specific isokinetic profile.